Effectiveness of interventions to promote pesticide safety and reduce pesticide exposure in agricultural health studies: A systematic review. - Maryam Afshari; Akram Karimi-Shahanjarini; Sahar Khoshravesh; Fereshteh Besharati (PLoS ONE)
Objective There is a relationship between pesticide exposure and farmworkers' health. Well-conducted evaluations can provide an insight into how to develop and implement more effective interventions to prevent farmers and farmworkers' exposure to pesticides. This review aimed to summarize the literature on the effectiveness of interventions to promote pesticide safety and reduce pesticide exposure among farmers and farmworkers. Methods A comprehensive search on PubMed, Embase, ISI Web of Science, Scopus, Science Direct, Agricola, NIOSHTIC, and Agris databases was performed to identify relevant studies published from 2000 to 2019. Randomized controlled trials (RCTs) and quasi-experimental studies assessing the effectiveness of interventions on a variety of outcomes related to pesticide exposure were considered. The searches were restricted to articles written in English. The methodological quality of included reviews was appraised using the Effective Public Health Practice Project quality assessment tool (EPHPP). Results The initial search led to 47912 records, 31 studies of which including nine RCTs and twenty-two quasi-experimental studies met the criteria. The majority of the included studies focused on the educational/ behavioral approach. The studies that applied this approach were effective in improving the participants' knowledge and attitude; however, these interventions were less effective in terms of making changes in participants' behaviors and their risk of exposure to toxic pesticides. Multifaceted interventions were moderately effective in terms of improving farmers' and farmworkers' behaviors and reduction in exposure to toxic pesticides. We did not find any studies that had evaluated the effectiveness of engineering/technological, and legislation/enforcement interventions. Conclusions Although the majority of studies were based on an educational/behavioral approach and did not assess the effect of interventions on objective measures, the results of this review highlight the significant effectiveness of educational programs and some potential key elements of these interventions. These findings may inform policymakers to develop interventions to reduce pesticide exposure among farmers and farmworkers.